2017
DOI: 10.1155/2017/3467593
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Benchmarking of Multisurface UHF RFID Tags for Readability and Reliability

Abstract: As the price of passive radio frequency identification (RFID) tags continues to decrease, more and more companies are considering item-level tagging. Although the use of RFID is simple, its proper application should be studied to achieve maximum efficiency and utilization in the industry. This paper is intended to demonstrate the test results of various multisurface UHF tags from different manufacturers for their readability under varying conditions such as orientation of tags with respect to reader, distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The readability of RFID tags has been analysed in the literature using various experimental approaches, followed by statistical analysis of the empirical data using regression models or other advanced techniques. The statistical analysis can be based on variability of the performance metrics of one tag [5], [6] or multiple tags [7], [8] versus the surrounding environment. This paper aims to analyse and quantify the degradation in the RFID communication link in a high-density context.…”
Section: Introductionmentioning
confidence: 99%
“…The readability of RFID tags has been analysed in the literature using various experimental approaches, followed by statistical analysis of the empirical data using regression models or other advanced techniques. The statistical analysis can be based on variability of the performance metrics of one tag [5], [6] or multiple tags [7], [8] versus the surrounding environment. This paper aims to analyse and quantify the degradation in the RFID communication link in a high-density context.…”
Section: Introductionmentioning
confidence: 99%
“… Limited empirical research that demonstrates the benefits of RFID in the healthcare sector [18,19]  The hype related to the adoption of new technology, which might slow the adoption process [20] because of related concerns, such as cost and technological issues  Technical complexity related to technology implementation [21,22]  Security and privacy challenges associated with adopting the technology [23,24]  Scarcity of publications on RFID adoption in the healthcare sector [25]  Unavailability of valid constructs that allow for the study of RFID adoption [26] An extensive review of studies that addressed the factors affecting RFID adoption revealed that most of these studies concentrated on respondents' perceptions of RFID implementation [27,28]. Others focused on specific factors or issues, such as staff management [29], organisational factors [30,31], privacy issues [23] and improvement of the reliability of RFID [32]. Some used existing frameworks, such as the technology-organisation-environment (TOE) framework [22] and the unified theory of acceptance and use of technology [25].…”
Section: Introductionmentioning
confidence: 99%